The stem cell inhibitor salinomycin decreases colony formation potential and tumor‐initiating population in docetaxel‐sensitive and docetaxel‐resistant prostate cancer cells. Issue 3 (13th December 2019) - Gruber, Martina; Handle, Florian; Culig, Zoran
Abstract: Background: Prostate cancer (PCa) is one of the most frequently diagnosed tumors in men. In general, therapies for localized PCa are curative. However, treatment of advanced PCa is considered palliative since development of therapy resistance occurs rapidly. It has been shown that tumor‐initiating cells are likely involved in therapy resistance. They are not eliminated by conventional therapies and thereby lead to tumor progression and relapse. The aim of this study was to evaluate the effects of the known stem cell inhibitor salinomycin on this critical subpopulation of cells. Methods: Expression of the cell surface markers CD24 and CD44 was assessed by immunofluorescence and fluorescence‐activated cell sorting. Colony formation efficiency and classification of colony types with varying tumor‐initiating potential (holoclones, meroclones, and paraclones) were analyzed in an automated way by the newly developed CATCH‐colonies software in the absence or presence of salinomycin. Results: Automated high‐resolution colony formation analysis consistently identified the various colony types in a broad range of PCa cell lines. Serial clonogenic assays confirmed that holoclones show the highest colony formation potential and maintain their tumor‐initiating capacity over multiple rounds. Furthermore, holoclones showed high expression of CD44, while CD24 was not expressed in these clones, thus representing the well‐described tumor‐initiating CD24 − /CD44 high population. Salinomycin decreased the CD24 − /CD44 high population in both docetaxel‐sensitive PC3 and docetaxel‐resistant (DR) PC3‐DR. Moreover, treatment of PC3, DU145, PC3‐DR, and DU145‐DR with salinomycin led to a significant reduction in the colony formation potential by targeting the colonies with high tumor‐initiating potential. Conclusions: Taken together, we demonstrated that salinomycin specifically targets the tumor‐initiating cell population in docetaxel‐sensitive and docetaxel‐resistant PCa cells and may represent a potential therapeutic approach for the treatment of advanced PCa.